117k views
3 votes
I need to know the right answer soon it’s due tonight

I need to know the right answer soon it’s due tonight-example-1
User Jiaaro
by
5.0k points

1 Answer

7 votes

Multiplying 9/8 and the first equation we get:


-(63)/(8)x-9y=(81)/(8)\text{.}

Adding the above equation and the second equation of the system we get:


-(63)/(8)x-4x=(81)/(8)-22.

Adding like terms, we get:


-(95)/(8)x=-(95)/(8)\text{.}

Therefore:


x=1.

Subtituting x=1 in the first equation, we get:


-7-8y=9.

Solving the above equation for y, we get:


\begin{gathered} -8y=9+7, \\ -8y=16, \\ y=-2. \end{gathered}

Answer:


x=1,\text{ y=-2.}

User Alek Davis
by
5.4k points